Chlorine Induces Physiological and Morphological Changes on Chicken Meat Campylobacter Isolates - Muhandiramlage, Gayani Kuriyawe; McWhorter, Andrea R.; Chousalkar, Kapil K. (Frontiers in Microbiology, 2020)
Broiler chickens frequently become colonized by Campylobacter species. As a consequence, Campylobacter, can enter the poultry meat supply chain and represents a significant risk for human public health. A number of on-farm biosecurity and processing measures are used to mitigate the load of Campylobacter on point-of-use chicken meat. In many countries, chlorine is commonly used as a biocide in processing plants to reduce bacterial loads on poultry carcasses but there is limited evidence of its effectiveness on Campylobacter. In this study, 116 Campylobacter isolates (89 C. jejuni and 27 C. coli) were isolated from poultry meat carcasses prior to the inside/outside wash step and used in in vitro assays exploring the efficacy of chlorine. A high proportion of isolates exhibited MIC and MBC values of 128 ppm but organic material present in the broth likely affect this result. Thus, additional bactericidal assays (time kill and chlorine inactivation) were used to characterize the response of C. jejuni isolates to different concentrations of chlorine. At 106 CFU, C. jejuni was found to be highly sensitive to concentrations of chlorine and was inhibited at low concentrations (0.2-2.0 ppm). At a higher bacterial load (108 CFU), variation in the response of different C. jejuni isolates was observed. One isolate was growth inhibited at 1.8 ppm while another required 16 ppm. At 108 CFU, C. jejuni could be resuscitated following chlorine to exposure highlighting a potential limitation of chlorine use. Analysis of UV leakage indicated that high chlorine concentrations resulted in increased 280 nm absorbance values suggesting bacterial membrane damage. Scanning electron and transmission electron microscopy were performed to characterize the morphological effects of chlorine exposure. Some effects of chlorine exposure included changes in shape (coccoid, or elongated), cellular degeneration, and shriveled bacterial cells. Interestingly, C. jejuni cells with normal morphology were also observed in the chlorine exposed group and represent a population of cells that could be resuscitated. This study is useful for the chicken meat industry and provides data for future optimization of chlorine use in reducing Campylobacter loads.